Pemanfaatan Media Pembelajaran Berbasis Nilai Kearifan Lokal Pada Siswa Sekolah Dasar di Kelurahaan Kisaran Baru - Zulham Siregar; Fadhli Ihsan Arbas Hasibuan; Widyaratnasari (Prodi Pendidikan IPS STKIP AL MAKSUM, 2026)
This Community Service (PkM) activity is motivated by the lack of use of local wisdom values in elementary school (SD) learning media in Kisaran Baru Village, which has an impact on the low cultural literacy of students. This socialization activity aims to provide understanding and direct experience to students and teachers regarding the use of learning media based on local Asahan Malay wisdom. The implementation method includes three stages: preparation through needs study, implementation in the form of interactive socialization and media demonstrations (educational comics and tradition-based game boards), and sustainability evaluation. The results of the activity showed very high enthusiasm, where 92% of students found it easier to understand local cultural values and 100% of teachers stated that this activity provided practical guidance in compiling contextual media. This socialization has proven to be effective in increasing students' interest in learning and cultural literacy, while supporting the strengthening of the Pancasila Student Profile at the basic education level.